Novel Transcriptional Biomarkers for Diagnosis and Prognosis of Sepsis - İNAN, Çağıl; TANRIÖVER, Mine Durusu; ERDEN, Didem DAYANGAÇ (Acta Medica, 2017)
Sepsis is a lethal disease that has a complex pathophysiology including a dysregulated inflammatory response, endothelial injury, microvascular thrombosis, vasoplegia and myocardial depression leading to multiorgan failure. Although there are advancements in the management of the disease, incidence and mortality rates are still high even in the developed countries. Prompt recognition of sepsis, early initiation of antibiotics, source control, optimal fluid and vasopressor therapy are of utmost importance. Currently, there is no gold standard biomarker that can allow clinicians to diagnose and prognosticate sepsis and to monitor the response to treatment in a precise, accurate and time efficient way. Current single-protein and multi-protein biomarkers have certain caveats and only partially helpful to diagnose and manage sepsis. Transcriptomics is a widely used approach for biomarker research, especially in sepsis. Technologies that apply to this area are easy, affordable and time efficient; further, the developments in next generation sequencing makes transcriptomics even more applicable. Even though the term transcriptomics includes all RNAs, microRNAs (miRNAs), which are short noncoding RNAs are especially under the spotlight for the search of sepsis biomarkers and some of them have already been validated to be specific. Specifically their high abundancy in circulation and their stability for long periods make them strong candidates for further research. Identification of new biomarkers can help enlightening the unknown sides of sepsis, which might lead to new therapeutic advancements in the management of the disease. Also the search for reliable biomarkers gives hope to clinicians and patients for a better management for this highly mortal and devastating condition. Key words: sepsis, prognosis, diagnosis, transcriptomics, biomarker, miRNA